Cross-cultural self-assertion and cultural politics: African migrants' writing in German since the late 1990s - Göttsche, Dirk (Wiley, 2010)
Since the 1980s African migrants’ writing in German has seen significant development, establishing itself as one of the few examples of a German postcolonial literature in the literal sense, undercutting traditional notions of national literatures, and contributing to the cross-cultural diversification of contemporary German literature. This essay combines an overview of this strand of African diasporic writing in German since the late 1990s with concise textual analysis of selected works in order to explore the authors’ engagement with experiences of postcolonial migration, their critique of colonial legacies in both Africa and Germany, and their intervention in German and transnational cultural debates. The discussion highlights discursive shifts in the history of this mostly autobiographical tradition as well as the emerging diversity of African voices, which challenges potential stereotypes about migrants’ writing.